1980
DOI: 10.1515/hfsg.1980.34.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Polymerisation of Water-Insoluble Lignins byFomes annosus

Abstract: Polymerization of Water-Insoluble Lignins by Fontes annosus SummaryKraft Lignin and spruce lignin (Björkman-Lignin) are partially polymerized when added to the cultures of Fomes annosus äs a Substrate in addition to glucose or cellobiose. The addition of either lignin resulted in a higher mycelial yield of the fungus and a specific secretion of laccase into the culture medium. Polymerization of lignin could be prevented by the addition of the laccase Inhibitors, e. g. thioglycolic acid or sodium azide to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…Additional evidence in favour of lignin polymerisation by laccase was revealed when the molecular weight of water-insoluble lignin increased on adding cultures of the fungus Fomes annosus. 18 Work performed by Ferm et al 19 involved laccase treatment of water-soluble lignosulfonates. Not surprisingly, a browning of the lignosulfonate solutions combined with an increase in the average molecular weight was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence in favour of lignin polymerisation by laccase was revealed when the molecular weight of water-insoluble lignin increased on adding cultures of the fungus Fomes annosus. 18 Work performed by Ferm et al 19 involved laccase treatment of water-soluble lignosulfonates. Not surprisingly, a browning of the lignosulfonate solutions combined with an increase in the average molecular weight was observed.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that laccase preferentially catalyzed the polymerization of lignin-related substrates, leading to the formation of lignin-analogue polymers. [13] The laccase-catalyzed polymerization of syringic acid involving elimination of carbon dioxide and hydrogen from the monomer gave poly(1,4-phenylene oxide). [14] Precise control of the polymer structure was achieved by the laccase-catalyzed polymerization of p-(tert-butyl)phenol in aqueous methanol.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes render phenolic compounds less toxic via degradation or polymerization reactions and/or cross-coupling of pollutant phenols with naturally occurring phenols (25,28,45). Several processes using laccases as well as immobilized laccases have been developed for the treatment of phenolic effluents and polycylic aromatic hydrocarbons (3,9,12,13).…”
mentioning
confidence: 99%